Dictionary Day: A Community-Driven Approach To Dictionary Compilation - Gelles, Bryan (My University, 2018)
A common component of language documentation is the compilation of a small dictionary. The method of compilation has changed very little in the last century: most documentarians elicit individual lexical items from a speaker and check the item through both translation and backtranslation with other speakers. Two major problems with this method are the absence of larger community engagement and idiosyncratic problems that come from lexical item elicitation. Animere is an endangered language spoken by around thirty speakers all aged over forty years. The speech community is located in Kecheibi, northern Volta Region, Ghana. Over a five month period I began the initial documentation of Animere with funds provided by a Small Grant from the Endangered Languages Documentation Programme, integrating Dictionary Day, one day a week when members of the community would gather to discuss lexical items. This method proved highly successful: I saved time and funds by making use of the speech community’s intuition while obtaining valuable folk linguistic information when there was disagreement. Furthermore, the speech community was not only engaged but agentive, allowing for genuine consultation between the linguist and the speech community. The major drawback, however, is lack of synergy among documentarians and other linguists when excluding prescribed data collection methods.
Keywords: Dictionary; dictionary compilation; community engagement